2019
DOI: 10.4103/apc.apc_42_18
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen in low doses for closure of the ductus arteriosus of the premature

Abstract: Objective: The objective of the study is to report the experience with acetaminophen in low doses as an alternative to the treatment of the ductus arteriosus of the preterm newborn. Materials and Methods: Retrospective study including preterm newborns with patent ductus arteriosus who received oral acetaminophen because treatment with indomethacin had failed or is contraindicated. A dosage consisted of a first dose of 25 mg/kg and maintenance doses of 30 mg/kg/day, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…A study by Guimarães et al showed that low dose oral acetaminophen (25 mg/kg initial dose followed by 30 mg/kg/day, for 3–7 days) is an effective replacement if indomethacin or ibuprofen failed or contraindicated. 22 …”
Section: Discussionmentioning
confidence: 99%
“…A study by Guimarães et al showed that low dose oral acetaminophen (25 mg/kg initial dose followed by 30 mg/kg/day, for 3–7 days) is an effective replacement if indomethacin or ibuprofen failed or contraindicated. 22 …”
Section: Discussionmentioning
confidence: 99%
“…We also observed that acetaminophen concentrations are more likely to be in the therapeutic range after first dose in late and very preterm neonates but not in the extreme preterm. Perhaps, a loading dose of acetaminophen at 20 mg/kg could possibly result in achieving the optimal therapeutic concentration as administered in some recent studies 30,31 . Intravenous acetaminophen at the dose administered in the present study is likely to result in a median exposure of 90 µmol/L as evident from one of the previous studies 32 .…”
Section: Discussionmentioning
confidence: 67%
“…During the study, it was observed that some preterm newborns needed a longer treatment period to achieve ductal closure, which prompted a readjustment to the protocol, and treatment duration was extended to 7 days. 12 Another clinical trial by Dash et al, obtained a ductal closure rate of 100% with a 7 day treatment with paracetamol. 13 Also El-Khuffash et al, compared long (7 days) to short (2 days) courses of oral paracetamol and obtained a better results with longer duration of treatment.14 Above studies are complementing with our study where we prescribed paracetamol for minimal 3 days to maximum 7 days and achieved a ductal closure of 91.7%.…”
Section: Discussionmentioning
confidence: 99%